The Structure of the Subjective Economic Well-being Depending on Its Level - V A Hashchenko (Peoples' Friendship University of Russia (RUDN University), 2008)
The article contains the new approach to studying the psychology of the economic well-being, i.e. structural-level. From its position the subjective economic well-being is revealed as polyphenomenological formation, the contents and specificity of which are defined by the natural organization of the system of its structural formations. The new data are submitted, allowing to establish and explain a number of features and laws of the organization of SEW.